Analisis Penerapan Strategi Segmenting, Targeting, Dan Positioning Dalam Memasarkan Produk-Produk Syariah Di PT. Sun Life Medan - Zulfitri Zulfitri; Zuhrinal M. Nawawi; Nuri Aslami (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Marketing strategy plays an important role in the company. The purpose of the marketing strategy is to determine and with the goals of the organization and implement its mission. One strategy that is often used is the strategy of Segmenting, Targeting and Positioning (STP). Segmenting means dividing a market into groups that have the same needs. Targeting is a matter of how to choose, select, and reach the market. Positioning is how the company puts the product it makes into the minds of consumers. Determining the marketing strategy both from segmentation, target and position is one of the company's weapons to face market competition. The right strategy will make it easier for companies to market their products. The method used in this study is a descriptive qualitative approach, which aims to find out how the implementation of segmenting, targeting and positioning strategies in marketing sharia products at PT. Sun Life Medan. The results of this study explain that PT. Sun Life Financial Medan has implemented segmentation based on demographics, psychographics, geography, behavior, target market and market position for each of its products. For the target itself, the company already has targets that are carried out in accordance with predetermined segments and also for its market position, it has emphasized the image of a different sharia agency.